Effectiveness of the Sensitive Nutrition Intervention Program in Accelerating Stunting Reduction in Baubau City - Andriani, Rininta; Islamy, La Ode Syaiful (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Stunting is a condition of failure to thrive in toddlers due to long-term malnutrition, exposure to repeated infections, and lack of stimulation. Not all short toddlers are stunted, so pediatricians need to differentiate them, but stunted children are scarce. Responding to this problem, the government issued Presidential Regulation (Perpres) Number 72 of 2021 concerning the Acceleration of Reducing Stunting. This regulation is a form of the government's commitment to accelerating the achievement of the stunting reduction target to 14 percent by 2024. This research aims to describe the effectiveness of a sensitive nutrition intervention program to accelerate stunting reduction in Baubau City, focusing on the accuracy of program targets and program outreach. The research used a qualitative design with a phenomenological approach. Data was collected through in-depth interviews with six informants, while secondary data came from related regional government organization (OPD) data. The data was then analyzed in several stages: data collection, reduction, presentation, and conclusion drawing. The research results show that based on indicators of the accuracy of program targets and program outreach in sensitive nutrition intervention programs, the acceleration of stunting reduction in Baubau City has been running effectively even though it has not significantly contributed to reducing the stunting prevalence rate. The decline in the stunting prevalence rate of only 1% shows that the accuracy of program targets still needs to be improved. Access to drinking water and sanitation, community recipients of PKH benefits, and the formation of farming community groups in the future must be several things that need to be maximized to achieve an accelerated reduction in stunting in Baubau City. In conclusion, the consistency of policy implementers must be bound by a shared commitment and shared goals and understanding in efforts to reduce the prevalence of stunting.